Menumbuhkan Nilai Kewirausahaan melalui Kegiatan Market Day - Setyawati, Wiwit; Aprilia, Erika Astriani; Syifa, Ahmad (Prodi Ekonomi Syariah Universitas Pamulang, 2023)
This community service (PKM) is in collaboration with SMP Islam Al-Azhar 25 South Tangerang. The purpose of conducting PKM activities is to provide understanding and direction to students of SMP Al-Azhar 25 South Tangerang about the importance of Growing entrepreneurship value through market day activities. The target audience for this PKM activity is the students, the total number of participants is 26 people with the activity scheduled for May 10, 2023. The methods used in this PKM are counseling or lectures, tutorials, discussions, and mentoring. The results of the PKM activities obtained data that market day activities have shown an increase in entrepreneurship values in the school. It is hoped that this PKM can be useful for many parties, especially for students of SMP Islam Al-Azhar 25 Middle School, South Tangerang.